Understanding the Pathogenesis of Angelman Syndrome through Animal Models - Nihar Ranjan Jana (Neural Plasticity)
Angelman syndrome (AS) is a neurodevelopmental disorder characterized by severe mental retardation, lack of speech, ataxia, susceptibility to seizures, and unique behavioral features such as easily provoked smiling and laughter and autistic features. The disease is primarily caused by deletion or loss-of-function mutations of the maternally inherited UBE3A gene located within chromosome 15q11-q13. The UBE3A gene encodes a 100 kDa protein that functions as ubiquitin ligase and transcriptional coactivator. Emerging evidence now indicates that UBE3A plays a very important role in synaptic function and in regulation of activity-dependent synaptic plasticity. A number of animal models for AS have been generated to understand the disease pathogenesis. The most widely used model is the UBE3A-maternal-deficient mouse that recapitulates most of the essential features of AS including cognitive and motor abnormalities. This paper mainly discusses various animal models of AS and how these models provide fundamental insight into understanding the disease biology for potential therapeutic intervention.